Government- Pulled Triple Helix for Supporting National Aircraft Industry in the Global Value Chain with Tipology Hierarchy - Ismail Muzakir, Muhammad Athar (Perspektif : Jurnal Ilmu Administrasi, 2019)
This study reconstructs the government- pulled triple helix for supporting national aircraft industry in the Global Value Chain (gvc) with tipology hierarchy. By employing Soft Systems Methodology (SSM), this research revealed that Triple Helix Model for development aircraft industry directed to design Macro Policy, revitalize test laboratories, strengthen aircraft financing policy, building supporting Industries and empower aerospace human resources. The government-pulled triple helix model has overlapping the role played by Academia (A), Busines (B), and Government (G) in the development of the aircraft industry. In fact, according to Etkowitz, H. (2008) that overlapping of role only occurs in university pushed triple helix model. In addition, the configuration of actor G in  the triple helix needed for development national aircraft industry is not generic but based on specific context. In aircraft development, especially for strengthening the aerospace industry cluster, the role of association is also important. In the GVC of Aircraft Industry with typology of hierarchy, PT DI is required to be able to build networks with industry partners, domestic and foreign research institutions and aircraft component industry associations. The Government will obtain lesson learnt on how the strategy for supporting the national aircrafts development such as program of N 219, N 245 or R 80 which developed at present.